Exploring pediatric surgery dissertations: Focus areas and future directions - Azizoglu, Mustafa; Kamci, Tahsin Onat (The European Research Journal, 2025)
Objectives: The aim of this study was to evaluate pediatric surgery dissertations included in the Higher Education Council dissertation database. Methods: A search was conducted in Turkey's Higher Education Council dissertation database using the keyword "pediatric surgery" to identify all dissertations published in the database between 2019 and 2023. The evaluation focused on dissertation topics. Results: A total of 120 dissertations were analyzed. The most common topics were related to the gastrointestinal system (n=37) and urology (n=30). Clinical studies showed an increasing trend over the years, rising from 53% in 2019 to 80% in 2022, before slightly decreasing to 72% in 2023. Experimental studies accounted for 47% of the studies in 2019 but declined to 20% in 2022, with a slight recovery to 28% in 2023 (P=0.242). Clinical studies dominated in most sections, particularly in traumatology (100%), thoracic surgery (86%), and general pediatric surgery (80%). Experimental studies had higher proportions in gynecology (60%) and urology (43%) (P=0.090). The most common topics were related to appendicitis (n=9), esophageal atresia (n=8), anorectal malformations (n=7), hypospadias (n=7), and testicular conditions (n=7). Dissertation top five topics accounted for 32% of all topics. Conclusions: Pediatric surgery dissertations mainly centered on clinical studies, with a notable focus on gastrointestinal and urological topics. Appendicitis, esophageal atresia, and anorectal malformations were the most studied areas. Regenerative medicine was significantly underrepresented. Encouraging studies in regenerative medicine and multidisciplinary approaches could drive innovation and address gaps in pediatric surgery research.